TYPES OF COMMUNICATION STYLES IN DONALD TRUMP SPEECH - Ridwan, Andi Khalil; Iskandar, Iskandar (Journal of English Literature and Linguistic Studies, 2024)
In this study, the researchers discussed the communication styles Donald Trump used when delivering his speech. The three speeches studied were Israel's capital is now Jerusalem, Coronavirus news conference and Radical islamic terrorism speech. This study aims to determine how the communication style is applied to Donald Trump's speech and what types of communication styles are most often used by Donald Trump. In determining this, researchers used the theory of Tubbs and Moss (1996). There are six types of communication styles in Tubbs and Moss theory, namely Equalitarian, Structuring, Controlling, Dynamic, Relinquishing and Withdrawal. Qualitative content analysis is a method of researching problems in this study. researchers found only four types of the six types of communication styles that have been proposed, the four types are Structuring, Controlling, Dynamic and Relinquishing. Dynamic style is the least used type of communication style, which is only found in the second speech. While the other three types dominate in every speech, especially the Controlling style which is the type of communication style most often used by Donald Trump.